O inconsciente junguiano sob a ótica do Espírito imortal: regeneração por meio do autoconhecimento - Giácomo, Marcos Flud (2022)
Contemporary man feels the need to (re)find himself. It Demands self-knowledge. It searches for a greater life goal which is filled with purposes aligned with a sense of accomplishment. Personal development through the confrontation with the unconscious, mapped by Jung in a self-experiment described in the Red Book, revealed that the individuation can and must be also achieved with the integration with the spirituality within us. The integral man – physical, mental and spiritual - who is born from this need associates the psychological experiences with the spiritual ones. The conscious connection of spirituality in each of us is made with the benefits of the knowledge of our psychological structure where the human Soul meets the unconscious, where the Spirit interacts with the psyche